Application of the Unified Theory of Acceptance and Use of Technology Approach to Analyze User Acceptance of Digital Banking Services - Anindya Pangestika, Mirza; Soleh; Majid, Jamaluddin; Wildan Nuryanto, Uli; Hadi, Syamsul (SEULANGA SYSTEM PUBLISHER, 2024)
The Purpose Of This Study Is To Ascertain The Degree Of User Acceptance Of Digital Banks And To Test Theories On The Variables That Affect Users' Approval Of These Financial Institutions. This Research Employs A Quantitative Methodology. Questionnaires, observations, and a literature review are used to gather data for this study. The Jabodetabek Area's digital bank customers make up the research population. Purposive Sampling Was The Method Utilized For This Study, And There Were 100 Respondents In All. Statistical Analysis And Demographic Analysis Make Up Data Analysis. The Researcher Conducted Demographic Analysis Using Microsoft Excel And Performed Statistical Analysis By Analyzing The Outer And Inner Models With The PLS-SEM Approach Using Smartpls. The Research Results Showed That The Behavioral Intention Variable Showed An Influence Of 80%, While The Use Behavior Variable Had An Influence Of 70%. Furthermore, The Factors Or Variables That Influence The Behavioral Intention Of Digital Bank Users Include Social Influence, Price Value, Perceived Credibility, Self-Efficacy, Facilitating Conditions, And Habit. Meanwhile, Factors Or Variables That Influence The Use Behavior Of Digital Bank Users Involve Facilitating Conditions, Habit, And Behavioral Intention. With Most Hypotheses Accepted, This Research Makes A Positive Contribution To Understanding The Factors That Influence User Acceptance Of Digital Banks.